Multiple sclerosis and thyroid disease: Case report of two patients and review of the literature [Multipl Skleroz ve Tiroid hastaliklari: İki olgu sunumu ve literatür bildirimi] - (:unkn) unknown (My University, 2008)
Thyroid disease is a frequently seen side effect during interferon treatment of Multiple Sclerosis (MS). Autoimmunity is a well-known pathogenetic factor of MS. Tyhroiditis, and other autoimmune diseases may be seen together with MS. Also, thyroiditis may be caused by interferon treatment for MS. This side effect is especially, diagnosed in first year of the treatment. Patients with thyroid disease are usually asymptomatic and diagnosed by laboratory findings. In this report, we describe two MS patients with interferon treatment; one with subclinical hypothyroidism and one with thyrotoxicosis due to drug induced thyroiditis.
Keywords: Interferons; Multiple Sclerosis; Thyroid disease